The Excavations at Nimrud (Kalḫu), 1953 - Mallowan, M. E. L.
Introduction — Progress of the 1953 Excavations (6 Areas Investigated): Burnt Palace; Wells in the NW Palace; Quay-Wall; Ziggurat Terrace; Private Houses; Outer Town — Excavations in the Burnt Palace — Objects Discovered: Foundation Boxes; Varia — Excavations in the NW Palace: Wells (Layard's Well in Room AB; Well in the Courtyard A).